Application of Demonstration Methods to Improve Learning Outcomes of Class X IPS Students of SMA Negeri 62 Central Maluku - Ratna Sari, Sri; Muhammadin Al Fath, Ayatollah (Journal of General Education Science, 2023)
This study aims to describe the application of the demonstration method, and the obstacles during the application of the demonstration method to improve student learning outcomes in class X IPS SMA Negeri 62 Central Maluku. This research is a type of classroom action research conducted in two cycles with four stages including planning, action, observation, and reflection. The research subjects were teachers and students of class X, totaling 35 students. Data collection techniques used in research are observation, tests, interviews, and field notes. The instruments used in this study were observation sheets, test sheets, interview sheets, and field note sheets. The results of observing teacher activity in cycle I was 2.6 increasing to 3.7% in cycle II. Then, the results of observing student activity in the first cycle were 67, 4 increased to 87.4 in cycle II. Data on the results of classical student learning completeness in cycle I showed that the percentage of students who completed learning was 59.4% and increased to 84.4% in cycle II. The obstacles encountered in cycle I and cycle II can be overcome properly. Based on the results of this study, it was concluded that the application of the demonstration method in class X SMA 62 Maluku can improve student learning outcomes.